Participação política a partir de iniciativas online: possibilidades, limites e desafios para a democracia - Ribeiro, Hanna Carvalho Lessa (2017)
In a context with questions about the legitimacy of traditional political models, digital technologies are being appropriated by members of civil society and government with the promise of increasing citizen political participation and modifying the current political system. However, the real possibilities of participation and the impact of the online platforms continue to be questions not definitive between the researchers. In order to identify the state of the art of the research field and deepening the theme, this dissertation proposes two Systematic Reviews of Literature (SRL) on cases of online initiatives created to allow and / or stimulate citizen participation in political issues, firstly in the world and then only in Brazil. The searches are carried out in the Web of Science, Scopus and DOAJ databases and their results are analyzed according to the characteristics of the articles and the platforms, their advantages and disadvantages for citizen participation, as well as a comparison between the global and national levels. Then, the 179 cases found in the articles in the two reviews are evaluated and organized in relation to the existing types of participation and their possible impacts on the political decision making. The main results suggest the existence of a rhetorical participation promoted by e-government portals, with top-down information flow and little or no influence on the decision-making process. It is concluded that online political participation goes beyond the technological issue and all social and political actors have responsibility for building a transparent, inclusive and collaborative democracy. It is suggested a new research agenda focused on the development of indicators to measure the impact and transparency of information, as well as further case studies on non-governmental initiatives that may bring relevant alternatives to the problems of online political participation.